Cloning and sequencing of the 18S-rRNA gene from Paphiopedilum helenae and Paphiopedilum micranthum - Thu Hue, Huynh Thi; Ha, Nguyen Hai; Hoang, Nguyen Huy; Hanh, Dang Van; Hai, Nong Van; Binh, Le Tran (Academia Journal of Biology, 2015)
Cloning and sequencing of the 18S-rRNA gene from Paphiopedilum helenae and Paphiopedilum micranthum